Female sex hormones and the recovery from exercise: Menstrual cycle phase affects responses - Hackney Anthony C.; Kallman Ashley L.; Ağgön Eser (Sciendo, 2019)
Study aim: Evidence supports female sex hormones have an influencing effect on amultitude of physiological and psychological systems related to exercise. Little is known, however, whether is effect persist into the recovery from exercise. Our objective was to examine aspects of muscle damage/inflammation process during recovery in healthy, exercise-trained women following endurance activity at the mid-follicular (MF; low sex hormone level) and mid-luteal (ML; elevated sex hormone levels) phases of their menstrual cycle.